2013
DOI: 10.1074/jbc.m113.505826
|View full text |Cite
|
Sign up to set email alerts
|

Two Major Facilitator Superfamily Sugar Transporters from Trichoderma reesei and Their Roles in Induction of Cellulase Biosynthesis

Abstract: Background:The molecular mechanism underlying the regulation of cellulase production by T. reesei is unclear. Results: The absence of sugar transporter Stp1 enhanced cellulase gene induction whereas the absence of Crt1 abolished cellulase gene expression. Conclusion: Crt1 is essential in cellulase gene induction independent of intracellular sugar delivery. Significance: These data shed light on the mechanism by which T. reesei senses and transmits cellulose signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
211
2
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 138 publications
(226 citation statements)
references
References 34 publications
9
211
2
4
Order By: Relevance
“…We also found that the function of three of the top scoring transporters had been studied previously (Huang et al, 2015;Ramos et al, 2006;Saloheimo et al, 2007;Zhang et al, 2013). One of them, TrStr1 (protID 50894) (Huang et al, 2015) was confirmed to function as xylose transporter, while Stp1 (protID 47710) and TrHxt1 (protID 22912) were associated to cellobiose and glucose utilization respectively (Ramos et al, 2006;Zhang et al, 2013).…”
Section: A Niger and T Reesei In Silico Proteome Miningsupporting
confidence: 67%
See 4 more Smart Citations
“…We also found that the function of three of the top scoring transporters had been studied previously (Huang et al, 2015;Ramos et al, 2006;Saloheimo et al, 2007;Zhang et al, 2013). One of them, TrStr1 (protID 50894) (Huang et al, 2015) was confirmed to function as xylose transporter, while Stp1 (protID 47710) and TrHxt1 (protID 22912) were associated to cellobiose and glucose utilization respectively (Ramos et al, 2006;Zhang et al, 2013).…”
Section: A Niger and T Reesei In Silico Proteome Miningsupporting
confidence: 67%
“…In this regard, the A. niger analyzing the T. reesei transcriptomic response to wheat straw, many of the HMM xylT top scoring transporters were upregulated on this carbon source versus glucose (Bischof et al, 2013;Ries et al, 2013). We also found that the function of three of the top scoring transporters had been studied previously (Huang et al, 2015;Ramos et al, 2006;Saloheimo et al, 2007;Zhang et al, 2013). One of them, TrStr1 (protID 50894) (Huang et al, 2015) was confirmed to function as xylose transporter, while Stp1 (protID 47710) and TrHxt1 (protID 22912) were associated to cellobiose and glucose utilization respectively (Ramos et al, 2006;Zhang et al, 2013).…”
Section: A Niger and T Reesei In Silico Proteome Miningsupporting
confidence: 55%
See 3 more Smart Citations